Immunological basis for enhanced immunity of nanoparticle vaccines - Hannah G Kelly; Stephen J Kent; Adam K Wheatley (Taylor & Francis Group, 2019)
Introduction: Immunization has been a remarkably successful public health intervention; however, new approaches to vaccine design are essential to counter existing and emerging infectious diseases which have defied traditional vaccination efforts to date. Nanoparticles (ordered structures with dimensions in the range of 1-1000 nm) have great potential to supplement traditional vaccines based upon pathogen subunits, or killed or attenuated microorganisms, as exemplified by the successful licensure of virus-like particle vaccines for human papillomavirus and hepatitis B. However, the immunological mechanisms that underpin the potent immunity of nanoparticle vaccines are poorly defined. Areas covered: Here, we review the immunity of nanoparticle immunization. The display of antigen in a repetitive, ordered array mimics the surface of a pathogen, as does their nanoscale size. These properties facilitate enhanced innate immune activation, improved drainage and retention in lymph nodes, stronger engagement with B cell receptors, and augmented T cell help in driving B cell activation. Expert opinion: In the near future, increasingly complex nanoparticle vaccines displaying multiple antigens and/or co-delivered adjuvants will reach clinical trials. An improved mechanistic understanding of nanoparticle vaccination will ultimately facilitate the rational design of improved vaccines for human health.